Risk factor consideration for the low power autonomous wind-mills based in the Ukrainian rural areas. - Сабо, Андрій Георгійович; Sabo, Andrii (Milan, Italy, 2023)
Off-grid wind turbines are a promising solution for generating clean and renewable energy in remote areas [1]. They should primarily be considered as a source of power supply in places where connection to the grid power supply would be impossible, difficult or rather expensive as well as a source of backup power supply in the event of a power outage for the critical consumers. That is why there is a growing interest among the farm owners in Ukraine to the possibilities of installing autonomous low power wind turbines [2, 3]. However, it is necessary to carefully weigh and take into account all risk factors in the design, acquisition, construction and direct operation of such wind turbines in order to make their installation economically justified. This article is devoted to these problems.
Міркування ризику для слабого вітру від мережі ферми.